2015
DOI: 10.1038/srep14771
|View full text |Cite
|
Sign up to set email alerts
|

Influence of H7N9 virus infection and associated treatment on human gut microbiota

Abstract: Between March and June, 2013, forty H7N9 patients were hospitalized in our hospital. Next-generation sequencing technologies have been used to sequence the fecal DNA samples of the patient, the within sample diversity analysis, enterotyping, functional gene and metagenomic species analysis have been carried on both the patients and healthy controls. The influence of associated treatment in H7N9 infected patients is dramatic and was firstly revealed in species level due to deep sequencing technology. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
98
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 26 publications
11
98
1
Order By: Relevance
“…Higher diversity and integrity of gut microbiota is favourable to the intestinal ecosystem 41,42 . According to recent research, viral infection can lower microbial diversity in the gut microbiota according to recent research [43][44][45] . Consistent with previous findings, in this study, our results demonstrated that NIBV infection decreases the diversity and richness of gut microbiota ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Higher diversity and integrity of gut microbiota is favourable to the intestinal ecosystem 41,42 . According to recent research, viral infection can lower microbial diversity in the gut microbiota according to recent research [43][44][45] . Consistent with previous findings, in this study, our results demonstrated that NIBV infection decreases the diversity and richness of gut microbiota ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota is an important factor responsible for interactions between these two sites in asthma (Marsland et al, 2015). In addition, the gut microbiota of patients with severe bacterial pneumonia (Chung, 2017), cystic fibrosis (Marsland et al, 2015), and influenza differs from that of healthy controls (Qin et al, 2015). Many studies show that early life is the most important period during which microbiota dysbiosis in the gut may lead to the development of many respiratory diseases, as the gut microbiota has a significant influence on immune cell maturation and resistance to pathogens .…”
Section: Gut-lung Axis Impacts On Respiratory and Gut Healthmentioning
confidence: 99%
“…Through further research involving metagenomic technology, the intestinal pathogenic bacteria Escherichia coli, Enterococcus faecium, and Klebsiella pneumoniae are enriched in the intestinal tract of patients, whereas the anti-inflammatory effect of Faecalibacterium prausnitzii is substantially reduced. The diversity of gut microbial species remarkably decreases in patients compared with that in healthy people [15]. Therefore, in the treatment of "four-anti-two balance" of patients with H7N9, the "antiintestinal microecological imbalance" treatment is emphasized, and a microecological regulator is used to reconstruct the intestinal microecological balance, which promotes the increase in the level of intestinal bifidobacteria, lactobacilli, and butyric acid-producing bacteria; minimizes secondary bacterial infections; and improves patient survival [14,16].…”
Section: Respiratory Infectious Diseases and Microecologymentioning
confidence: 99%